2019
DOI: 10.2147/ott.s214529
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Estrogen Receptor Beta Inhibits The Proliferation, Migration, And Angiogenesis Of Gastric Cancer Cells Through Inhibiting Nuclear Factor-Kappa B Signaling</p>

Abstract: PurposeThis study aimed to investigate the regulatory roles of estrogen receptor beta (ERβ) on gastric cancer (GC) cells, and reveal the potential mechanisms relating to nuclear factor-kappa B (NF-κB) signaling.MethodsGC cell lines SGC7901 and MKN45 were transfected with pEGFP-C1-ERβ to overexpress ERβ, and treated with PMA (a NF-κB activator) to activate NF-κB signaling. The cell proliferation and migration, as well as the formation of vessel-like structures in human venous endothelial cells (HUVECs) were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that ERβ can suppress canonical NFκB/p65 signaling in various cell and tissue types, however the mechanism(s) remains unclear and these effects have not been studied in TNBC 48 52 . Mechanistically, we provide evidence that ERβ does not alter the upstream signaling pathways required for p65 activation, nor does it impact p65 phosphorylation or nuclear localization.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ERβ can suppress canonical NFκB/p65 signaling in various cell and tissue types, however the mechanism(s) remains unclear and these effects have not been studied in TNBC 48 52 . Mechanistically, we provide evidence that ERβ does not alter the upstream signaling pathways required for p65 activation, nor does it impact p65 phosphorylation or nuclear localization.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cell migration plays important roles in angiogenesis, wound healing, and endothelial injury healing. 45,51,52 Therefore, we studied the effects of OGD/R and apelin-13 on endothelial cell migration. In the early stage of reperfusion (R16 h and R24 h), OGD/R decreased the migration capacity of cells, suggesting that reperfusion injury prevents migration by endothelial cells at the early stage.…”
Section: Discussionmentioning
confidence: 99%